Analysis of the Oil and Petrochemical Integrated Refinery Development Plan's environmental impact and its mitigation of public health status - Endang Susilowati; Sukriyanti Kustanti Moerad; Deti Rahmawati; Niken Prasetyawati (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2022)
Development is a social process that aims to enhance the environmentand the quality of communal life. Sustainability happens as a result ofthe environment serving as a living space and a source of additionalvalue. The following environmental factors must be integrated into adevelopment plan: biogeophysics, social, economic, cultural, and publichealth. PT PERTAMINA (Corporate Company) in collaboration withRosneft Oil Company will build and operate a new oil and petrochemicalintegrated refinery and its supporting facilities. About 27,000 peoplewere hired for the building phase, and about 3,000 for the operationphase. This study aims to lessen the detrimental effects of developmentplans on public health. This qualitative study is a cross-sectionaldescriptive investigation of the area surrounding the proposed refineryin East Java Province, Indonesia's Jenu District and Tuban Regency.The study's findings were determined through firsthand observationand a poll of 100 residents who would be impacted by the developmentplan. The findings show that, to prevent environmental disputes,environmental management and monitoring must be carried out.